2020
DOI: 10.1093/schbul/sbaa179
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Schizophrenia from an Evolutionary Perspective: An Association Study of Recent Evolutionary Markers and Schizophrenia

Abstract: The persistence of schizophrenia in human populations at a high prevalence and with a large heritability estimate despite reduced fertility and increased mortality rate is a Darwinian paradox. This may be likely if the genomic components that predispose to schizophrenia are also advantageous for the acquisition of important human traits, such as language and cognition. Accordingly, an emerging group of genomic markers of recent evolution in humans, namely human accelerated regions (HARs), since our divergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Interestingly four HAR variants that showed association with schizophrenia in our previous study (Bhattacharyya et al 2020) also showed significant association in several cognitive function GWAS; with rs3800926 strongly associated (P-value 6.1E-06) in a meta general cognition GWAS (Supplementary Table 12). This particular SNP showed nominal association across all GWASs of related traits, namely neurocortism, intelligence, and educational attainment (Supplementary Table 12).…”
Section: Associated Hpo Phenotypes With the Mapped Genes And Transcription Factorsmentioning
confidence: 62%
See 2 more Smart Citations
“…Interestingly four HAR variants that showed association with schizophrenia in our previous study (Bhattacharyya et al 2020) also showed significant association in several cognitive function GWAS; with rs3800926 strongly associated (P-value 6.1E-06) in a meta general cognition GWAS (Supplementary Table 12). This particular SNP showed nominal association across all GWASs of related traits, namely neurocortism, intelligence, and educational attainment (Supplementary Table 12).…”
Section: Associated Hpo Phenotypes With the Mapped Genes And Transcription Factorsmentioning
confidence: 62%
“…FUMA-SNP2GENE module was used to map SNPs to genes using three approaches have been used for mapping: (i) Positional, (ii) eQTL and (iii) Chromatin interaction as previously described (Bhattacharyya et al 2020) (Supplementary Methods).…”
Section: ) (Supplementary Methods)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the third topic comprises research on HARs’ involvement in psychiatric disorders. Most of the studies are focused on SCZ [ 66 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ], but there is also research on other neurodevelopmental psychiatric disorders and phenotypes, such as autism spectrum disorders (ASD) [ 52 , 58 , 66 ], bipolar disorder [ 76 ], and delirium syndrome [ 77 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human-accelerated regions (HAR) are genomic segments which have undergone accelerated nucleotide sequence change in humans relative to other primates. The most recent analyses suggest that there are 3,171 HARs in the human genome ( Pollard et al, 2006a , 2006b ; Prabhakar et al, 2006 ; Bird et al, 2007 ; Bush and Lahn, 2008 ; Lindblad-Toh et al, 2011 ; Hubisz and Pollard, 2014 ; Gittelman et al, 2015 ) HARs overlap regulatory elements important for brain development and are particularly related to elements active in the fetal brain ( Won et al, 2019 ; Bhattacharyya et al, 2021 , 2022 ; Cheung et al, 2022 ). Recently, massively parallel assay for regulatory element activity showed that 49% of HARs feature neurodevelopmental enhancer activity in human neural cells in vitro ( Girskis et al, 2021 ).…”
Section: Human Accelerated Cis -Regulatory Element...mentioning
confidence: 99%